(untitled) - World Fish Centre (ICLARM) (Thailand, 2001)
International Symposium on Women in Asian Fisheries presents a record of the 1998 symposium. The fisheries sector has unique problems related to women, which have to be addressed not only from a technical standpoint but also from a social one. The symposium is aimed at stimulating discussion and promoting well-planned research and development activities in this area.
Keywords: Women fishers,Fisheries,Thủy sản,Ngư dân, Phụ nữ